Diffusion tensor imaging findings of patients with parkinson’s disease refractory to medical treatment (Annals of Medical Research, 2021)
Aim: Diffusion Tensor Imaging (DTI) findings can be useful to detect and measure neurodegeneration that is seen in Parkinson’sdisease (PD). Microstructural changes in regions of the brain related with motor function are evaluated by using DTI measurementsof fractional anisotropy (FA) to find out the possible role of the technique in diagnosis in patients with PD.Materials and Methods: The study includes 18 PD patients who were candidates for deep brain stimulation surgery, and 19 controlgroup patients. DTI was performed in all cases. DTI characteristics of FA were measured in primary motor cortex (M1), supplementarymotor area (SMA), inferior parietal lobule, putamen (P), globus pallidus externus (GPe) and internus (GPi), ventrolateral nucleus ofthalamus (Th), substantia nigra (SN), cuneus, precuneus and cerebellar dentate nucleus (D) bilaterally. Additionally, we processed“raw” FA images and colored them according to fiber orientation to visualize STN and GPi nuclei.Results: Mean age of the control group was 59.2±13.2 (range: 31-79) years, while it was 56.7±16 (range: 42-77) years for the patientgroup. Mean duration of PD was 12.4±7.1 (range: 5-30) years. Study group FA values were significantly lower than the control groupin all areas bilaterally (p